2020 vision – An overview of prospects for diabetes management and prevention in the next decade. (September 2018) - Wang, Chih-Yuan; Neil, David L.; Home, Philip
Abstract: After a century of medical progress, people nowadays live longer with diabetes than ever before. However, current preventative approaches, compounded in part by increased life-expectancy, are failing to reduce the prevalence of diabetes. Cardiovascular sequelae account for many of the four million deaths annually attributable to diabetes. Evidence indicates that certain glucose-lowering medications can improve vascular outcomes in some people with type 2 diabetes, which, together with better understanding of using multiple therapies concurrently, offers opportunities for beneficial personalization of medication regimens. However, further well-designed long-term studies are needed to evaluate cardiovascular benefits and safety of new and older medications, particularly in users typical of everyday diabetes care. Although there are numerous other promising advances in pharmacotherapies and biotechnology, these will probably be unaffordable for most people with diabetes globally. Therefore, effective national public health approaches will be essential to reducing the incidence of diabetes and its associated burdens; these may entail politically controversial measures to change unhealthy lifestyle behaviours. Stakeholders could learn from past failures and emulate successes in other health-care initiatives. Without early action at all levels, we face a future in which approaching one-quarter of humans will have diabetes, with more than half afflicted during their lifetime.